Negotiating Shakespearean Meaning: the Case of Manga - Tatu Oana (Philologica Jassyensia, 2024)
While Shakespeare, as the epitome of high culture, has been ubiquitous in the Western canon for centuries now, the gap between having him there, within easy reach, and actually accessing the meaning of Shakespeare’s work grew larger and larger by the day. This study stems from a genuine need, that of making Shakespeare accessible, particularly to the younger generation, a need which has lately brought about a variety of Shakespearean adaptations, interpretations, translations. It is a plea for considering, primarily for educational purposes, a special type of Shakespearean re-visitation, let us call it, namely manga Shakespeare. In our increasingly visual culture, visual literacy tends to become a prerequisite, hence manga, as a form of transmedial adaptation, seems to be perfectly suitable to the transmission of Shakespeare, given that in his plays there is a sort of verbal-visual core that can be unpacked in an unexpected way in our modern times. Despite its complexity and its ability to afford double access (Gripsrud, 1989) to high and popular culture alike, manga Shakespeare is still considered an unworthy relative of the original. Therefore, an ancillary objective of this study is that of dismantling some of the most popular objections raised to the authenticity, usefulness and quality of manga adaptations in general, by setting fragments from three editions of manga Hamlet (SelfMadeHero 2007, Wiley 2008, and Manga Classics 2022) against the original text, observing the fresh formal and content embodiment, admitting the loss, but also the gain of achieving ideational transmission and accessibility to different times and audiences.
Keywords: Shakespeare; manga; re-visitation; adaptation; popular culture; high culture; transmedial